The Che Guevara Volunteer Work Brigade, and how I was inspired by solidarity to travel to Cuba! - Solanki, Janine (Canadian Woman Studies/les cahiers de la femme, 2025)
As I sit down to write about the Che Guevara Volunteer Work Brigade to Cuba and my experiences in solidarity travel to Cuba, it’s with the anticipation and excitement of embarking on my next trip to Cuba in a few short days, which will be my 13th time travelling to the island. I’ll soon be again experiencing what it’s like to move through a society that is working to build a better and more just world. I always enjoy those both simple and profound interactions with the Cuban people, from doctors to students, taxi drivers to artists, that remind me how Cuba’s revolutionary path is a beacon of hope in a world with far too much injustice. As Cuba continues to inspire me today, I’m often reminded of my first experience travelling to Cuba in 2006 with the Che Guevara Volunteer Work Brigade, as a high school student, which was an experience that truly changed the trajectory of my life.